Effect of Mind Sound Resonance Technique (MSRT - A yoga-based relaxation technique) on psychological variables and cognition in school children: A randomized controlled trial - U.S. Anusuya; Sriloy Mohanty; Apar Avinash Saoji (Elsevier, 2021)
Objective: School children undergo stress, which could impact their psychological functions and cognitive abilities. Yoga practices have been found useful in enhancing psychological functions and performance. The current study was planned to evaluate a yoga-based relaxation technique's efficacy as an extracurricular activity on psychological state and cognitive function. Design and setting: This study was a parallel-group randomized controlled trial conducted at a government school in south India. Participants: Sixty students with age ranging between 14-16 years (mean age ± SD; 15.3 ± 0.71 years) satisfying the inclusion and exclusion criteria were randomized to experimental and control groups with an allocation ratio of 1:1. Intervention: Experimental group received Mind Sound Resonance Technique (MSRT), whereas the control group performed supine rest (SR) for two-weeks. Outcome measures: Participants were assessed with State trait anxiety inventory - short form, Mind Wandering Questionnaire, State Mindfulness Attention Awareness Scale, and Trail making task at baseline and post-intervention. Results: Experimental group showed a reduction in state anxiety and mind wandering with improvement in state mindfulness and performance in the Trail-making task compared to the control group. Conclusion: Results of the current trial indicate the beneficial role of MSRT in enhancing psychological and cognitive functions in children. Further, large-scale trials are warranted to ascertain the usefulness of the technique.